A Novel AX+/BX− Paradigm to Assess Fear Learning and Safety-Signal Processing with Repeated-Measure Designs - Kazama, Andy M. (2013)
One of the core symptoms of anxiety disorders, such as Post-Traumatic Stress Disorder is the failure to overcome feelings of danger despite being in a safe environment. This inability likely stems from an inability to fully process safety signals, which are cues in the environment, that enable healthy individuals to over-ride fear in aversive situations. Studies examining safety signal learning in rodents, humans, and non-human primates currently rely on between-groups designs. Because repeated-measures designs reduce the number of subjects required, and facilitate a broader range of safety signal studies, the current project sought to develop a repeated-measures safety-signal learning paradigm in non-human primates. Twelve healthy rhesus macaques of both sexes received three rounds of auditory fear-potentiated startle training and testing using an AX+/BX− design with all visual cues. Cue AX was paired with an aversive blast of air, whereas the same X cue in compound with another B cue (BX) signaled the absence of an air blast. Hence, cue B served as a safety signal. Once animals consistently discriminated between the aversive (AX+) and safe (BX−) cues, measured by greater startle amplitude in the presence of AX vs. BX, they were tested for conditioned inhibition by eliciting startle in the presence of a novel ambiguous combined cue (AB). Similar to previous AX+/BX− studies, healthy animals rapidly learned to discriminate between the AX+ and BX− cues as well as demonstrate conditioned inhibition in the presence of the combined AB cue (i.e. lower startle amplitude in the presence of AB vs AX). Additionally, animals performed consistently across three rounds of testing using three new cues each time. The results validate this novel method that will serve as a useful tool for better understanding the mechanisms for the regulation of fear and anxiety.